Review of the MEPAG Report on Mars Special Regions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
Planetary protection is a guiding principle in the design of an interplanetary mission, aiming to prevent biological contamination of both the target celestial body and the Earth. The protection of high-priority science goals, the search for life and the understanding of the Martian organic environment may be compromised if Earth microbes carried by spacecraft are grown and spread on Mars. This has led to the definition of Special Regions on Mars where strict planetary protection measures have to be applied before a spacecraft can enter these areas. At NASA's request, the community-based Mars Exploration Program Analysis Group (MEPAG) established the Special Regions Science Analysis Group (SR-SAG2) in October 2013 to examine the quantitative definition of a Special Region and proposed modifications to it, as necessary, based upon the latest scientific results. Review of the MEPAG Report on Mars Special Regions reviews the conclusions and recommendations contained in MEPAG's SR-SAG2 report and assesses their consistency with current understanding of both the Martian environment and the physical and chemical limits for the survival and propagation of microbial and other life on Earth. This report provides recommendations for an update of the planetary protection requirements for Mars Special Regions.
Keywords: Space and Aeronautics

Preventing the Forward Contamination of Mars - National Research Council (The National Academies Press, 2006)
Recent spacecraft and robotic probes to Mars have yielded data that are changing our understanding significantly about the possibility of existing or past life on that planet. Coupled with advances in biology and life-detection techniques, these developments place increasing importance on the need to protect Mars from contamination by Earth-borne organisms. To help with this effort, NASA requested that the NRC examine existing planetary protection measures for Mars and recommend changes and further research to improve such measures. This report discusses policies, requirements, and techniques to protect Mars from organisms originating on Earth that could interfere with scientific investigations. It provides recommendations on cleanliness and biological burden levels of Mars-bound spacecraft, methods to reach those levels, and research to reduce uncertainties in preventing forward contamination of Mars.
Keywords: Space and Aeronautics

The Quarantine and Certification of Martian Samples - National Research Council (The National Academies Press, 2002)
One of the highest-priority activities in the planetary sciences identified in published reports of the Space Studies Board's Committee on Planetary and Lunar Exploration (COMPLEX) and in reports of other advisory groups is the collection and return of extraterrestrial samples to Earth for study in terrestrial laboratories. In response to recommendations made in such studies, NASA has initiated a vigorous program that will, within the next decade, collect samples from a variety of solar system environments. In particular the Mars Exploration Program is expected to launch spacecraft that are designed to collect samples of martian soil, rocks, and atmosphere and return them to Earth, perhaps as early as 2015.International treaty obligations mandate that NASA conduct such a program in a manner that avoids the cross-contamination of both Earth and Mars. The Space Studies Board's 1997 report Mars Sample Return: Issues and Recommendations examined many of the planetary-protection issues concerning the back contamination of Earth and concluded that, although the probability that martian samples will contain dangerous biota is small, it is not zero.1 Steps must be taken to protect Earth against the remote possibility of contamination by life forms that may have evolved on Mars. Similarly, the samples, collected at great expense, must be protected against contamination by terrestrial biota and other matter. Almost certainly, meeting these requirements will entail opening the sample-return container in an appropriate facility on Earth-presumably a BSL-4 laboratory-where testing, biosafety certification, and quarantine of the samples will be carried out before aliquots are released to the scientific community for study in existing laboratory facilities. The nature of the required quarantine facility, and the decisions required for disposition of samples once they are in it, were regarded as issues of sufficient importance and complexity to warrant a study by the Committee on Planetary and Lunar Exploration (COMPLEX) in isolation from other topics. (Previous studies have been much broader, including also consideration of the mission that collects samples on Mars and brings them to Earth, atmospheric entry, sample recovery, and transport to the quarantine facility.) The charge to COMPLEX stated that the central question to be addressed in this study is the following: What are the criteria that must be satisfied before martian samples can be released from a quarantine facility?
Keywords: Space and Aeronautics